Tradition unveiled: a comprehensive review of microbiological studies on Portuguese traditional cheeses, merging conventional and OMICs analyses - Serrano, Susana; Morais, Susana; Semedo-Lemsaddek, Teresa (Frontiers in Industrial Microbiology, 2024)
The microbial communities inhabiting Portuguese traditional cheeses play a fundamental role in shaping their unique flavor, texture, and safety characteristics. This comprehensive review synthesizes findings from both conventional microbiological studies and advanced OMICs analyses to provide a deeper understanding of the microbiota dynamics in these cheeses. We explore the microbial composition, diversity, and functional roles of bacteria, yeasts, and molds across various Protected Designation of Origin (PDO) cheeses, highlighting their contributions to cheese ripening, flavor development, and safety.Additionally, we discuss the potential of OMICs technologies, namely metagenomics, in unraveling the complex microbial ecosystems of Portuguese traditional cheeses. Through this integrative approach, we aim to shed light on the intricate interplay between microorganisms and cheese matrices, unveiling the secrets behind the rich heritage and distinctiveness of Portuguese traditional cheeses.